CommunityCare Free Medical Clinic: A Model of an Entirely Student-Driven Free Clinic in Your Backyard - Addison Sparks; Sydney Hatch; Yvonne Ogrodzinski; Claire Stoll; Vaishnavi Aradhyula; Richard Paat (Journal of Student-Run Clinics, 2025)
Student-run free clinics improve health care access for underinsured patients in the United States.  This descriptive report delves into our unique, entirely student-led model aimed at deliver-Ing healthcare services to underserved communities and how our model combines many services offered at other student-run free clinics. According to the 2022-2023 Lucas County Community Health Assessment, 6% of Lucas County, Ohio, adults were uninsured, with 12% of Black adults being uninsured. Targeting this historically underserved demographic informed the location of some of our clinic sites. To ensure that our student-led initiative maintains the same quality as a federally-funded clinic, we prioritize working in interprofessional teams of students and providers. To reduce the burden of transportation, we also seek to provide as many on-site ancillary ser-vices as possible, such as vision screening and point-of- care lab testing. Additionally, we provide extensive medical trainee education focused on integrating inclusivity, cultural sensitivity, and patient advocacy. We seek to provide a cost-effective, replicable clinic model and empower the next generation of medical trainees to advocate for underserved communities across the United States.